KEAWETAN 52 JENIS KAYU INDONESIA - Ginuk Sumarni; Mohammad Muslich (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
Fifty two Indonesian wood species were collected from forest areas in Indonesia for durability test. The samples measuring 60 cm (in length) by 5 cm (width) by 5 cm (height) were prepared. The durability's field test was conducted at Cikampek experimental forest using a graveyard method. The samples were vertically but partially buried lengthwise in the soil, leaving behind 10 cm upright still exposed to the air. The spaces (distances) between the buried samples were 15 cm. Assessment on the buried samples (stacks) was carried out once after the succession of each 6-month interval. The assessment involved the degrees of attack by termites and the depth (extent) of decay inflicted by particular fungi. Afterwards, the 52 wood species as each represented by their tested stacks/samples could be categorized into five durability classes. Most of the samples were severely attacked by termites. Forty nine out of 52 wood species (i.e. 94 percent) were attacked by termites. Meanwhile, the remaining 3 wood species (Glochindion philippicum Robins., Blumeodendron kurzii J.J. S.M. and Myristica lognifes Ward.) were attacked by the decaying fungi. Therefore, those three species were categorized as durability class V. In total, there were 33 wood species (63,4 percent) that belonged to durability class V, 17 wood species (32,6 percent) as class IV and 2 wood species (3,8 percent) as class III. Since none can be categorized as durability class I or II. the preservative treatment is necessary for the overall 52 wood species. The species categorized as durability class III were rengas manuk (Gluta wallichii (Hook f Ding Hou) and kempas (Koompasia malaccensis Maing.).